Significant linkage to migrane with aura on chromosome 11q24 - Cader, Z; Noble-Topham, S; Dyment, D; Cherny, S; Brown, J; Rice, G; Ebers, G (2003)
Migraine with aura (MA) is a prevalent neurological condition with strong evidence for a genetic basis. Familial hemiplegic migraine, a rare Mendelian form of MA, can be caused by mutations in the calcium channel gene, CACNA1A or in the ATP1A2 gene, a Na+/K+ pump. Susceptibility genes for the more prevalent forms of migraine have yet to be identified despite several reports of linkage including loci on 4q24, 1q31, 19p13 and Xq24-28. We have undertaken a genome-wide screen of 43 Canadian families, segregating MA with families chosen for an apparent autosomal dominant pattern of transmission. Diagnosis was based upon International Headache Society Criteria. Parametric linkage analysis revealed a novel locus on 11q24 with a two-point LOD score of 4.2 and a multi-point parametric LOD score of 5.6. We did not find any support for linkage at previously reported loci. The lack of consensus amongst linkage studies, including this study, is probably an indication of the heterogeneity that is inherent for MA. Nevertheless, the finding of a highly significant locus with a LOD score of 5.6 is powerful evidence that a gene increasing susceptibility to MA resides on 11q24. Several candidate genes map to this region of the genome including a number of iion channel genes such as GRIK4, SCNB2, KCNJ5 and KCNJ1.